Pentapeptide‐rich peptidoglycan at the Bacillus subtilis cell‐division site. Issue 2 (6th February 2017) - Morales Angeles, Danae; Liu, Yun; Hartman, Alwin M.; Borisova, Marina; de Sousa Borges, Anabela; de Kok, Niels; Beilharz, Katrin; Veening, Jan‐Willem; Mayer, Christoph; Hirsch, Anna K.H.; Scheffers, Dirk‐Jan
Summary: Peptidoglycan (PG), the major component of the bacterial cell wall, is one large macromolecule. To allow for the different curvatures of PG at cell poles and division sites, there must be local differences in PG architecture and eventually also chemistry. Here we report such local differences in the Gram‐positive rod‐shaped model organism Bacillus subtilis . Single‐cell analysis after antibiotic treatment and labeling of the cell wall with a fluorescent analogue of vancomycin or the fluorescent D‐amino acid analogue (FDAA) HCC‐amino‐D‐alanine revealed that PG at the septum contains muropeptides with unprocessed stem peptides (pentapeptides). Whereas these pentapeptides are normally shortened after incorporation into PG, this activity is reduced at division sites indicating either a lower local degree of PG crosslinking or a difference in PG composition, which could be a topological marker for other proteins. The pentapeptides remain partially unprocessed after division when they form the new pole of a cell. The accumulation of unprocessed PG at the division site is not caused by the activity of the cell division specific penicillin‐binding protein 2B. To our knowledge, this is the first indication of local differences in the chemical composition of PG in Gram‐positive bacteria. Abstract : The large macromolecule peptidoglycan, that forms the bacterial cell wall, contains local differences in architecture and chemistry that encode the shape of the wall. We used different probes to label peptidoglycan in combination with antibiotics treatments, to show that peptidoglycan at the cell division site of Bacillus subtilis is enriched in unprocessed stem peptides. This work provides the first indication of non‐homogeneous peptidoglycan chemistry in Gram‐positive bacteria.